Perioperative Temperature Monitoring and Management to Maximize Patient Safety: A Quality Improvement Project - Jones, Rachel (My University, 2022)
Appropriate temperature monitoring and management is an important part in optimizing patient success in the operative theatre. Perioperative hypothermia remains a threat to patient morbidity and mortality and consistent measures for thermoregulation are needed. The purpose of this quality improvement project was to assess anesthesia providers’ perceptions of the effectiveness of their current practice for intraoperative temperature monitoring and of a newly developed intraoperative temperature monitoring educational tool. Invited participants in this project were Certified Registered Nurse Anesthetists (CRNAs) who took a short pre-intervention questionnaire assessing temperature monitoring knowledge, listened to a recorded educational PowerPoint presenting a newly developed educational tool, and completed a post-intervention questionnaire after the two-week implementation period concluded. Findings suggested that the intervention alerted the CRNAs to the existing AANA national temperature monitoring standard. There was also an improvement in the time required for the CRNAs to locate a reference of evidence-based guidelines to answer any questions they had regarding best practice for perioperative temperature monitoring, as well as an increase in provider confidence in their knowledge. Limitations of this project involved the short project timeline and small sample size. Four participants reflect only a small portion of the anesthesia department at the participating facility. For future projects, more attention could be focused on educating CRNAs on proper temperature monitoring technique and best current practice. Additionally, the organization itself could provide future educational material disbursed to include the current national guidelines.
Keywords: perioperative; hypothermia; nurse anesthetist